Analysis of the Efficiency of Swallow Cultivation as an Agribusiness Effort in Society - A. Besse Dahliana; R. Taufiq Nur Muftiyanto; Sitti Normawati; Muhamad Habib; Rosa Zulfikhar (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to analyze the efficiency value of swallow cultivation as an agribusiness effort in the community in Bone Regency. The demand for swallow nests on the world market is still very high, so to meet market demand, people are starting to try to cultivate swallows by building swallow houses, including in Bone Regency. Every business, including the swallow business, is certainly not free from various risks, especially in terms of financial risks, even though the production volume is quite high. Therefore, swallow breeders must know the analysis of the business they are carrying out, not only limited to how to maintain and cultivate swiftlets to produce nests as the main product of production. This research uses quantitative research methods with data collection techniques using questionnaires distributed to 30 wallet bird entrepreneurs. The results of the research prove that the business efficiency value for swiftlet cultivation in Bone Regency with a period of 1 - 4 years is 12. Meanwhile, businesses with a period of more than 5 years obtain a value of 23. This explains that the swiftlet cultivation business in Bone Regency has been implemented. efficient because the R/C Ratio value is > 1, meaning that every Rp. 1 of costs incurred in the swiftlet cultivation business over a business period of 1 – 4 years will generate Rp. 12. Meanwhile, businesses with a business period of more than 5 years will generate revenues of IDR. 23.